2016
DOI: 10.1039/c6dt02074g
|View full text |Cite
|
Sign up to set email alerts
|

Non-covalent functionalization of WS2 monolayer with small fullerenes: tuning electronic properties and photoactivity

Abstract: Atomically thin two-dimensional transition metal dichalcogenides (TMDCs) heterostructures have recently attracted growing interest due to their massive potential in solar energy applications due to their band gap in the visible spectral range and extremely strong light-matter interactions. Herein, heterostructures composed of WS2 and MoS2 monolayers, as representative TMDCs, with small fullerenes (B12 and C20) are investigated to explore their applications in solar energy conversion using first principles calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…In photocatalytic systems, fullerene can create a space potential difference to enrich the separation and migration of the photogenerated charge carriers, as well as tuning the band gap . The amount of charge transfer in WS 2 /fullerenes and MoS 2 /fullerene (C 60 , C 26 , and C 20 ) heterostructures was found to depend on the nature of the fullerene. In addition, a type‐II staggered band alignment, which was formed in the MoS2/C20 and WS2/fullerenes heterostructures, contributed to the enriched photocatalytic performance and the reduced charge recombination.…”
Section: Recent Progress In the Design Of Semiconductor Photocatalystmentioning
confidence: 99%
“…In photocatalytic systems, fullerene can create a space potential difference to enrich the separation and migration of the photogenerated charge carriers, as well as tuning the band gap . The amount of charge transfer in WS 2 /fullerenes and MoS 2 /fullerene (C 60 , C 26 , and C 20 ) heterostructures was found to depend on the nature of the fullerene. In addition, a type‐II staggered band alignment, which was formed in the MoS2/C20 and WS2/fullerenes heterostructures, contributed to the enriched photocatalytic performance and the reduced charge recombination.…”
Section: Recent Progress In the Design Of Semiconductor Photocatalystmentioning
confidence: 99%
“…In this regard, boron-nanostructure-based heterostructures or devices with desirable performance for various fields are worth the expectation, similar to its analogues of carbon, which have widely been used in recent years. Carbon-based heterostructures are the focus of intense research in the past decades and have revealed that the interfacial interaction is one of the key factors to govern their properties and applications. , However, the investigations of boron nanostructures are so far concentrated in their structures and related properties, and even seldom research studies focus on their growth on substrates, , let alone their interaction and its effect. This impedes not only the experimental preparation of low-dimensional boron structures but also the design of novel boron-based devices.…”
Section: Introductionmentioning
confidence: 99%
“…Then, fullerene could enhance the light absorption (both UV and visible light) because it is an excellent photo-response material (300~700 nm), wherein elevated light energy utilization excites more electrons from VB to CB [ 33 , 34 ]. In respect to photo-response characteristics, it must also be mentioned that fullerene could not shift the adsorption edge of pristine photocatalyst unless the introduction of fullerene changed the structure of semiconductor [ 35 , 36 , 37 ]. In other words, if the fullerene does not change the crystalline structure of semiconductor in the synthesis procedure, which was typically affected by a stronger bonding force other than simply physically blending, it could not change the conduction band (Eg) at all.…”
Section: Role Of Fullerenementioning
confidence: 99%